2000
DOI: 10.1086/315711
|View full text |Cite
|
Sign up to set email alerts
|

Once‐Daily Combination Therapy with Emtricitabine, Didanosine, and Efavirenz in Human Immunodeficiency Virus–Infected Patients

Abstract: The safety and efficacy of a once-daily regimen that combines emtricitabine, didanosine, and efavirenz was studied among 40 previously untreated human immunodeficiency virus (HIV)-infected patients. The median plasma HIV RNA level was 4.77 log(10) copies/mL at baseline and decreased by a median of 3.5 log(10) copies/mL at 24 weeks, with 98% and 93% of patients achieving plasma HIV RNA levels <400 and <50 copies/mL, respectively. The median CD4 cell count was 373 cells/microL at baseline and increased by a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 12 publications
5
62
0
Order By: Relevance
“…In western cohorts, one-half of patients have these symptoms at initiation of efavirenz therapy but these symptoms usually resolve within 1 month. 79 A study from Haiti found that 46 (10%) of 452 patients discontinued efavirenz therapy because of persistent neurotoxicity. 52 A study from Coˆ te d'Ivoire also found a high neurotoxicity rate (69%) after initiation of efavirenz therapy.…”
Section: Neuropsychiatric Disordersmentioning
confidence: 99%
“…In western cohorts, one-half of patients have these symptoms at initiation of efavirenz therapy but these symptoms usually resolve within 1 month. 79 A study from Haiti found that 46 (10%) of 452 patients discontinued efavirenz therapy because of persistent neurotoxicity. 52 A study from Coˆ te d'Ivoire also found a high neurotoxicity rate (69%) after initiation of efavirenz therapy.…”
Section: Neuropsychiatric Disordersmentioning
confidence: 99%
“…10 The efficacy of a once-daily regimen including FTC, ddI EC, and EFV was confirmed in adults both in a pilot study and a randomized, open-label trial. 11,12 Efficacy of FTC 6 mg/kg once daily in pediatric patients has been reported in 3 abstracts. One non-randomized study replaced 3TC with FTC in 82 patients, both treatment-experienced and treatment-naïve, ages 4 months to 16 years.…”
Section: Efficacymentioning
confidence: 99%
“…83 A once-daily combination therapy of emtricitabine with didanosine and efavirenz has proven safe and both antivirally and immunologically effective for at least 24 weeks. 84 Emtricitabine has been considered an ideal drug candidate 85 in that it shows synergism with other antiretrovirals, excellent tolerability, a long intracellular half-life supportive of once-daily dosing, and in comparison with lamivudine, 4-to 10-fold higher in vitro potency against HIV. (14) has in vitro activity against both HIV and HBV; it is converted by adenosine deaminase to dioxolane guanine (DXG), which is then phosphorylated intracellularly to DXG 5 0 -triphosphate, the active metabolite.…”
Section: R E V E R S E T R a N S C R I P T A S E ( R T ) I N H I B mentioning
confidence: 99%